HOW TO ENGAGE STUDENTS IN READING (Web of Teachers: Inderscience Research, 2024)
In this article, strategies of engaging students in reading are analyzed in learning new language. Also, this article shows that using interactive techniques more often can make a class more effective and give some useful recommendations and suggestions.